The new european union global strategy: how to meet foreign and security policy challenges? - Garcia, Francisco Proença (2021)
EU faces identitarian problems and his loosing international rele-vance, having decided to approve a new Global Strategy, having as the main tool a flexible and adaptable geopolitical CSDP. To complement is strategic role it should enhance is capabilities (military and civilian).